The Relation between Financial and Housing Wealth of Dutch Households - Stefan Hochguertel; Arthur van Soest (Uppsala University, Department of Economics, 1998)
We analyze households' joint investment decisions for financial wealth and homes. We use a bivariate censored regression model with endogenous switching. Fixed costs or transaction costs are captured by an unobserved nonzero censoring threshold. The model allows for spill-over effects of a binding threshold for one asset on the demand for the other asset. We find that tenure choice affects the level of financial wealth. Our results do not support the view that people first accumulate financial wealth before acquiring homes.This can be due to the absence of down payments constraints in the Netherlands.
urn:nbn:se:uu:diva-2426
Keywords: C34; D12; G11; R21; 330; Housing demand; Household saving; Portfolio choice; Limited dependent variables